(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
For centuries, John Milton’s depiction of Satan inParadise Lost has fallen under two categories of critical analysis. One camp,which over the years included such literary and theologian critics as C.S.Lewis and Stanley Fish, has stated that Milton used Satan as a means to explainGod’s mysteries to man. Another camp that had equal sway and included poetWilliam Blake and William Empson held that Satan’s vivid and empatheticportrayal was evidence of Milton’s subconscious alliance with "the devil’scamp." Satan’s rousing speech during the Devil’s council in Book Two givessome weight to this argument. But, whether one agrees or disagrees with thesetwo different interpretations, one cannot argue against the fact that Milton’sportrayals of God and Satan are the most vivid of any in the Western canon. While one can also examine these portrayals from anhistorical, biographical, or theological point of view, what I am mostinterested in is how these two characters hold up as literary creations and howthey mirror one another in terms of identity and the perceptual concepts ofself-definition.